Implementation of Argumentative Driven Inquiry in Science Learning 2009-2023: Bibliometric and Review Analysis - Misbah, Misbah; Hamidah, Ida; Sriyati, Siti; Samsudin, Achmad (Tarbiyah : Jurnal Ilmiah Kependidikan, 2024)
This research examines research trends in applying argumentation-driven inquiry (ADI) in science learning and its potential for future research. A literature review is used in this research method through bibliometric analysis. The data source was obtained from the Scopus database, which obtained 72 articles from 549 articles in 2009-2023 with the keyword "Argumentative Driven Inquiry." The results show that publications fluctuate every year, with some years seeing a significant increase in publications, while others show a decline. Articles on this topic mostly come from international journals indexed by Scopus with quartile 1. This is in line with sources that publish many articles on this topic. Similarly, the top authors based on publications also come from international journals indexed by Scopus with quartile 1. The US and Indonesia are the most productive countries on this topic. The visualization results are divided into 6 clusters. It can find specific keywords that have the potential to be further researched in the future.